Analysis of sandwich rolling with two different thicknesses outer layers based on slab method. (February 2016) - Wang, H.Y.; Li, X.; Sun, J.; Wang, Z.H.; Zhao, D.W.; Zhang, D.H.
Abstract: When the thicknesses of the outer layers are different in sandwich rolling, based on the different kinds of arrangements with the hard and soft materials the thickness ratio of two outer layers is changed differently during the rolling process. After the first analysis of the different outer thicknesses sandwich rolling, the rules for final thickness ratio of the two outer layers are proposed. In soft–hard–soft sheets (s–h–s) the thickness ratio of outer layers is remained in the final bonded sandwich sheet however in hard–soft–hard sheets (h–s–h) the thickness ratio is alleviated by sandwich rolling itself. A model based on slab method is proposed to analyze this phenomenon and 4 groups of experiments with Al and Cu as well as steel are conducted. The results calculated by the model well agree with those measured in the experiments. Then the accuracy and worthy of the model are verified. Highlights: It is the first time that the different outer thicknesses sandwich rolling is researched with analytic method. Based on the different arrangements of the soft and hard materials, the different outer thicknesses ratio is remained in the final bonded sheet (soft–hard–soft), but this ratio is lessen in the bonded sandwich sheet (hard–soft–hard). Experiments are conducted with Al–Cu–Al, Cu–Al–Cu and Al–steel–Al as well as steel–Al–steel, the model is verified by the results measured from the experiments. The rolling forces calculated by this model are also verified by the results recorded in the references.